1994
DOI: 10.1121/1.410233
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of nonlinear effects in a driven vibrating wire

Abstract: Experimental measurements have been made of the motion of a red brass harpsichord wire driven electromagnetically in a fixed direction perpendicular to the equilibrium position of the wire. The motion is complex compared to that predicted by simple linear theory because of effects due to tensional changes and longitudinal motions. Optoelectronic detectors are used to measure amplitude and phase of the transverse motions as functions of the driving frequency, both in the driving direction y and the direction z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Secondly, the particular sound of some musical instruments can be explained by some nonlinearities, such that they appear as a case where nonlinear resonances between numerous eigenfrequencies should be key to properly understand their dynamical behavior. The string is obviously the most common case for string instruments sharing the two properties of nonlinear vibrations together with commensurable eigenfrequencies; see, e.g., [12,17,18,32]. Nonlinearities are also encountered in reed instruments such as saxophone and clarinette; see, e.g., [27] and brass instruments (see, e.g., [20]) and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the particular sound of some musical instruments can be explained by some nonlinearities, such that they appear as a case where nonlinear resonances between numerous eigenfrequencies should be key to properly understand their dynamical behavior. The string is obviously the most common case for string instruments sharing the two properties of nonlinear vibrations together with commensurable eigenfrequencies; see, e.g., [12,17,18,32]. Nonlinearities are also encountered in reed instruments such as saxophone and clarinette; see, e.g., [27] and brass instruments (see, e.g., [20]) and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…For the neo-Hookean material (β = 1/2) we obtain the Hill equation 9) and the related Mathieu equation .7) is unstable for any value of * . In figure 1 we plot, for different values of λ S , v R versus β at the 2 : 1 resonance.…”
Section: Linear Wavesmentioning
confidence: 80%
“…In such an experiment a periodic change in the longitudinal tension of a taut string resonantly parametrically excites transverse waves when the frequency of the change of the tension is close to twice the natural frequency of the transverse waves. The simplicity of this physical system has generated an enormous literature from the experimental (e.g., Hanson et al, 1994) and theoretical side (e.g., Rowland, 1994), starting from the considerations of Lord Rayleigh summarized in his book on acoustics (Strutt, 1945).…”
Section: = µ(T)x + F (Z T) Y = µ(T)y + G(z T) Z = λ(T)zmentioning
confidence: 99%
“…Legge and Fletcher described the coupling of vibrating modes in a one-polarization wave motion and demonstrated the generation of missing harmonics as a result of this coupling [19]. Hansen et al experimented with coupling of polarizations and reported measured results of amplitudes and phase differences of transversal components under forced motion [20]. More interestingly, they found nonlinear coupling of the two transversal polarizations even at vibration displacements of only a few microns.…”
Section: Introductionmentioning
confidence: 93%
“…For the single-delay-loop model, the varying delay is . By substituting for and for in (17), we obtain (20) Parameter may be solved from (20) as (21) Similarly, we may estimate the maximum average elongation using (21) if is known. An example of the determination of the parameter follows.…”
Section: B Estimation Of Parameters For the Tension Modulation Modelmentioning
confidence: 99%